Bactericidal effect of photocatalytically‐active nanostructured TiO2 surfaces on biofilms of the early oral colonizer, Streptococcus oralis. Issue 8 (12th June 2017) - Westas, Emma; Hayashi, Mariko; Cecchinato, Francesca; Wennerberg, Ann; Andersson, Martin; Jimbo, Ryo; Davies, Julia R
Abstract: This study evaluated the photocatalytic bactericidal effect of nanostructured anatase‐rich titanium dioxide (TiO2 ) on microbial biofilms. Commercially pure titanium discs were spin‐coated with photocatalytic TiO2 nanoparticles (P25). Uncoated discs were used as control (CTRL). Half of the CTRL and half of the P25‐coated surfaces were coated with purified saliva (SAL) to give four different groups (CTRL, CTRL + SAL, P25 and P25 + SAL). Streptococcus oralis were allowed to form biofilms on the discs for 18 h and non‐adherent cells were rinsed off. Bacterial viability was assessed at time 0 with Live/Dead BacLight staining and epifluorescence microscopy. The remaining discs were divided into a non‐UV group and UVA‐irradiated (+UV) group (irradiation time, 6 or 24 h). Thereafter, viability was assessed as above. Viability at time 0 was high and no dead cells were seen on any of the surfaces, even after 24 h, in the absence of UVA. However, after 24 h of exposure, the proportion of viable cells was reduced by 40% on the P25 discs compared to 0 and 6 h, and this effect was enhanced with a salivary pellicle. Members of mixed species biofilms differ in their susceptibility to the bactericidal effect of the surfaces tested and further investigations are needed to optimize the conditions. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2321–2328, 2017.